MASALAH DEWASA MADYA HIDUP MENJANDA DAN UPAYA MENGATASINYA (Studi di Kenagarian âKâ Pesisir Selatan) - Murniati, Murniati; Sano, Afrizal; Nita, RahmaWira (Bimbingan dan Konseling, 2014)
Dewasa madya life divorcee in Kenagarian âKâ Pesisir Selatan the result their husband pass away broken merry cause more problems of their life. This research is purepose to describe some problems: (1) ekonomi, (2) social, (3) families, (4) practice, (5) seksual and (6) where their live and how to overcome. This research is the kualitative research describtion, infrom in this research is dewasa madya in the divorcee is four people and informan supporter is four children, mother and they nearest family. Data to collected through observastion, interview and documentation. The data accurancy to the test to used triangulation data and analysis with interactive model of consist data reduction to serve and to take conclusion. The result of the research to show that: (1) in generally they have a problem about trade income, domestic animals and farm, (2) the social life be distrubed and they keep be parient about that. (3) the family problem, they feeling about to educate their children but keep importancy priority their children, (4) they have to pursue about practice problem and several they request to the they nearest family, (5) the problem about sexsualitas, they felt very lonely and have desire to merried again, while they have traumatic about that, (6) the problem about their residence is in generally they have and household equipment yet complet to they need. However they keep to expedient for can good useful about what they have.Â